Birth weight and blood pressure: cross sectional and longitudinal relations in childhood. - Whincup, P. (BMJ Group, 1995)
OBJECTIVE--To examine cross sectional and longitudinal relations between birth weight and blood pressure in childhood. DESIGN--Cross sectional study of primary school children aged 9-11 years, with analysis in relation to previous measurements at 5-7 years in a subgroup. SETTING--20 primary schools in Guildford and Carlisle. SUBJECTS--1511 children measured at 9-11 years (response rate 79%), including 549 who had been measured at 5-7 years. MAIN OUTCOME MEASURES--Blood pressure at 9-11 years, change in blood pressure between 5-7 and 9-11 years, birth weight (based on maternal recall), and placental weight (based on birth records). RESULTS--At 9-11 years birth weight was inversely related both to systolic blood pressure (regression coefficient -2.80 mm Hg/kg; 95% confidence interval -3.84 to -1.76) and to diastolic blood pressure (regression coefficient -1.42 mm Hg/kg; -2.14 to -0.70) once current height and body mass index were taken into account. Placental weight was inversely related to blood pressure after adjustment for current height and body mass index but placental ratio (placental weight to birth weight) was unrelated to blood pressure. Between 5-7 and 9-11 years systolic blood pressure rose more rapidly in children of lower birth weight (regression coefficient -1.71 mm Hg/kg; -3.35 to -0.07). This effect seemed to be stronger in girls. CONCLUSIONS--Birth weight rather than placental ratio is the early life factor most importantly related to blood pressure in childhood. The results support the possibility of "amplification" of the relation between birth weight and blood pressure, particularly in girls.